1993
DOI: 10.1210/jcem.76.5.8496311
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-four-hour growth hormone (GH)-releasing peptide (GHRP) infusion enhances pulsatile GH secretion and specifically attenuates the response to a subsequent GHRP bolus.

Abstract: GH-releasing peptide (GHRP; SK&F 110679) is a synthetic hexapeptide that specifically stimulates GH release through nonopiate non-GH-releasing hormone (non-GHRH) receptors. To determine the effects of a 24-h GHRP infusion, eight normal young men received infusions of saline for 2 h, then saline (on two occasions) or GHRP (1.0 micrograms/kg.h; on two occasions) for 24 h, followed by an iv bolus of GHRP or GHRH (1.0 micrograms/kg) and a 2.5-h saline infusion. Serum GH was measured every 10 min throughout the 28.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
1

Year Published

1995
1995
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 29 publications
4
31
1
Order By: Relevance
“…This finding is very much in keeping with the lowered pulse amplitude observed in the present study following inhibition of GHS-1a receptor activation. Several studies have also demonstrated that administration of GH-releasing peptides or GHSs will amplify the normal pulsatile pattern of GH in both young and elderly human subjects (23,24). These findings are consistent with the concept that endogenous ghrelin acts through the GHS-1a receptor to amplify the normal pulsatile pattern of GH secretion.…”
Section: Use Of Bim-28163 To Dissect the Role Of Endogenous Ghrelin -supporting
confidence: 73%
“…This finding is very much in keeping with the lowered pulse amplitude observed in the present study following inhibition of GHS-1a receptor activation. Several studies have also demonstrated that administration of GH-releasing peptides or GHSs will amplify the normal pulsatile pattern of GH in both young and elderly human subjects (23,24). These findings are consistent with the concept that endogenous ghrelin acts through the GHS-1a receptor to amplify the normal pulsatile pattern of GH secretion.…”
Section: Use Of Bim-28163 To Dissect the Role Of Endogenous Ghrelin -supporting
confidence: 73%
“…The effects of continuous peripheral infusion of synthetic GHS on pulsatile GH release in the human mirror the foregoing outcomes (11,41,45,73).…”
Section: Simulation Of Continuous Peripheral Ghrelin Stimulationmentioning
confidence: 72%
“…Fifth, continuous intravenous GHS infusion amplifies GH pulse amplitude (but not frequency) 5-to 30-fold in both men and women (11,41,45,73). Therefore, augmentation of GH peak height is an expectation of valid model performance.…”
Section: Ghrelin and Gh Network: Basis Of Model Structurementioning
confidence: 99%
“…GH administered by osmotic minipumps induces a continuous increase in circulating GH concentrations, whereas the GHSs, also when administered continuously, increase the amplitude of the endogenous GH pulses (Huhn et al 1993, Jaffe et al 1993. Furthermore, it has been suggested that different subtypes of the recently cloned GHS receptor may exist and that different GHSs may differ in their binding affinity for the different subtypes (Ong et al 1998).…”
Section: Tablementioning
confidence: 99%